2001
DOI: 10.1016/s0370-2693(01)00381-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent result from E821 experiment on muon g−2 and unconstrained minimal supersymmetric Standard Model

Abstract: Recently, the E821 experiment at the Brookhaven National Laboratory announced their latest result of their muon g − 2 measurement which is about 2.6-σ away from the standard model prediction. Taking this result seriously, we examine the possibility to explain this discrepancy by the supersymmetric contribution. Our analysis is performed in the framework of the unconstrained supersymmetric standard model which has free seven parameters relevant to muon g − 2. We found that, in the case of large tan β, sparticle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The constraint on m A is deduced from the absence of Z → hA (either by direct observation or as inferred from the measured width of the Z), which implies that m A > ∼ 80 GeV. 11 Finally, in a general 2HDM, m H ± > ∼ 78.7 GeV [21]. One noteworthy consequence of m h ∼ 10 GeV is the possibility of mixing between the h and the 0 ++ bb bound states χ b0 (1P ) and χ b0 (2P ), as discussed in refs.…”
Section: Final Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The constraint on m A is deduced from the absence of Z → hA (either by direct observation or as inferred from the measured width of the Z), which implies that m A > ∼ 80 GeV. 11 Finally, in a general 2HDM, m H ± > ∼ 78.7 GeV [21]. One noteworthy consequence of m h ∼ 10 GeV is the possibility of mixing between the h and the 0 ++ bb bound states χ b0 (1P ) and χ b0 (2P ), as discussed in refs.…”
Section: Final Results and Conclusionmentioning
confidence: 99%
“…Moreover, the MSSM provides additional mechanisms for generating significant contributions to δa NP µ . A number of recent papers [7,8,9,10,11] have shown that the recent BNL measurement is compatible with supersymmetric contributions to δa NP µ involving chargino and neutralino exchange, over an interesting region of MSSM parameter space.…”
Section: Introductionmentioning
confidence: 95%
“…The maximum allowed value for ͉͉ is taken to be 1000 GeV. The contours are shown from bottom to top for tan ␤ϭ2, 3,6,10,20,30,40,50. The black bars on the right vertical axes indicate the 1and 2-allowed regions from the Brookhaven E821 experiment.…”
Section: Susymentioning
confidence: 99%
“…Predictions for a SUSY Ϫa SM in dilaton-dominated supergravity models with various tan ␤ϭ2,3,6,10, 20, 30,40 ͑from bottom to top͒, as a function of the lighter chargino mass and the lighter smuon mass. All charged superpartners are required to have mass above 100 GeV.…”
mentioning
confidence: 99%
“…out over the recent months [35,36,37,38,39] exploring the effects of the g − 2 constraint become more stringent but a significant part of the parameter space is still allowed [37].…”
Section: Many Further Investigations Of the Implications Of The Bnl Rmentioning
confidence: 99%